SEMG frequency of the erector spinae in children with lesions scoliotic - Jacek Wilczyński; Natalia Habik-Tatarowska; Marta Mierzwa-Molenda; Aneta Sowińska; Alicja Kasprzak; Magdalena Kabała; Żaneta Wypych; Rafał Zieliński (Kazimierz Wielki University, 2018)
The aim of the study was to analyze the frequency of SEMG rectifier spine in children with scoliosis. Analysis electromyographic rectifier spine was performed using a 12-channel camera Noraxon TeleMyo DTS. The shape of the spine was assessed using optoelectronic Diers formetric III 4D. The research was Carried out in the Posturology Laboratory at the Faculty of Medicine and Health Sciences, UJK in Kielce (Poland). In the group of children with scoliosis curvature of the most frequently occurred on the location of the rib. In girls, it represented (62%) in boys (56%). In boys, thoracic scoliosis twoarched right-handed and left-sided lumbar were 19 (30%). The largest absolute differences in the frequency of EMG rectifier spine in girls with scoliosis group occurred lying ahead for the variable lumbar left (S = 36, 99). In turn, the value of the variable lower limbs up the right side of the lumbar was absolutely the most diverse among boys in the group of scoliosis (S = 40.54). Univariate analysis of variance indicated that there are significant differences in the measurements of intra-frequency variable SMEG rectifier spine torso upright thoracic among boys (p = 0.04). This means that the values of the variables were significantly different between groups attitudes scoliotic, scoliosis and normal boys, and the value of the significance level was less than 0.5 (p